Standardization of Retort pouch processed mini chevon patties incorporated with sesame seed paste - Jeyapriya, S; Pal , U K; Rajkumar , V; Mandal , P K; Kasthuri , S (Journal of Meat Science, 2024)
There is increasing demand for ready to eat shelf stable meat products, which has easy marketing potential. In this study, an attempt was made to standardise the process schedule for retort processed chevon patties. In our earlier study Chevon patties were prepared for convenience and variety by adding sesame seed paste (SSP) at 2.8%. The control and patties with SSP were used to standardize retort pouch processing schedule. The product core temperature reached its first lethality rate of 0.001, when the product core temperature was 940C, retort temperature was 1210C in treatment 1, in treatment 2 they were 920C and 1180C, and in treatment 3 they were 900C and 1140C, respectively. Treatment 3 required a heating time of 15 minutes, cooling time of 7 minutes and total lethality (F0) of 11.093. The heating lag factor (Jh) was 1.10 and the cook value was 73.26 min. The cooling lag factors (jc) were 1.00, 1.10 and 1.20 for treatments 1, 2 and 3, respectively.Thefh/U ratio of mini chevon patties product were 2.80, 2.24 and 1.93 for treatments 1,2 and 3, respectively. The highest heating rate index, heating lag factor, heating time, cook value and time for sterilization and lowest fh/U values were recorded in treatment 3. The patties processed withF0 of 11.093 had better sensory scores and the packets were not spoiled for a month on visual observation.
Keywords: Retort pouch; Chevon patties; Sesame seed paste; heat penetration characteristics; thermal processing